Establishing histopathological criteria for breast cancer research - Werbach, Andrea (2021)
Breast cancer is a heterogeneous disease with varied morphological appearance, molecular features, behavior and response to therapy. Though these varieties are well-established and rely on clinical and histopathological classification, research demands the continuous study of the ever-increasing knowledge on the mechanisms behind disease progression and associated risk factors.